1986
DOI: 10.1203/00006450-198604000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Response of Human Milk Leukocytes to Chemoattractant Peptides

Abstract: ABSTRACT. To test the hypothesis that neutrophils and macrophages in human milk may not defend by classical inflammatory mechanisms, experiments were conducted to ascertain whether adherence, orientation, and directed motility of these leukocytes would be enhanced by exposure to chemoattractant peptides including N-formyl-L-methionyl-L-phenylalanine and N-formyl-L-methionyl-L-leucyl-L-phenylalanine and C5a generated from zymosan activated human serum. Adherence and spatial orientation were tested on coverglass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
25
1
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 31 publications
5
25
1
1
Order By: Relevance
“…Recent studies indicated that certain functions of HM neutrophils and macrophages are altered compared to their counterparts in human peripheral blood (PB). The adherence, orientation, and directed movement of HM neutrophils and macrophages were significantly less than those of PB neutrophils and monocytes after stimulation with chemoattractants such as N-formylmethionyl peptides and C5a [48]. In contrast, in vitro experiments utilizing a type 1 collagen gel assay demonstrated that the spontaneous motility of HM macrophages was much greater than that of PB mononuclear cells [331.…”
mentioning
confidence: 99%
“…Recent studies indicated that certain functions of HM neutrophils and macrophages are altered compared to their counterparts in human peripheral blood (PB). The adherence, orientation, and directed movement of HM neutrophils and macrophages were significantly less than those of PB neutrophils and monocytes after stimulation with chemoattractants such as N-formylmethionyl peptides and C5a [48]. In contrast, in vitro experiments utilizing a type 1 collagen gel assay demonstrated that the spontaneous motility of HM macrophages was much greater than that of PB mononuclear cells [331.…”
mentioning
confidence: 99%
“…Furthermore, the adher-collagen was precipitated by the addition of an equal volume of ence and directed movement of human milk macrophages are 20% (w/v) NaC1. The precipitate was pelleted by centrifugation not increased by chemoattractant agents (12). This suggested that at 3000 X g for 1 h, washed, and resuspended in 3% acetic acid special populations of blood monocytes may be attracted to the to achieve a final concentration of 1.2 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Additional experimental observations supported those possibilities. In contrast to the lack of movement of neutrophils in human milk (12)(13)(14), it was discovered that HMM spontaneously moved more rapidly than blood monocytes in a three-dimensional, type I collagen matrix (1 5).In this study, the genesis of the increased motility of human milk macrophages was investigated. We tested whether circulating systemic factors produced early in lactation, mammary gland tissue factors, or constituents in human milk up-regulated the motility of blood monocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The phagocytes may be able to generate toxic oxygen radicals, but they are not upregulated by chemoattractant agents (50). Furthermore, the neutrophils d o not move well in vitro (50,51), whereas the macrophages migrate readily into three-dimensional matrices (5 1). Perhaps, the two classes of ~haaocvtes in human milk have a dichotomy of function.…”
mentioning
confidence: 99%